Spectrophotometric Determination of Trace Amounts of Hydrazine by the Inhibition of the Alizarin Navy Blue Reaction - TABATABAEE, MASOUMEH; A. ENSAFI, ALI; BABAEI, MARYAM (Asian Journal of Chemistry, 2010)
In this proposed method a simple kinetic method is described for the determination of trace amounts of hydrazine, which is based on its inhibition effect on the reaction between alizarin navy blue and sodium nitrite. The reaction was monitored spectrophotometrically by measuring the change in absorbance of alizarin navy blue at 530 nm. The calibration graph was linear in the range of 0.10-1.40 μg/mL hydrazine, with a limit of detection of 0.09 μg/mL. The relative standard deviation for ten replicate measurements of 0.60 and 1.00 μg/mL hydrazine were 2.2 and 1.5%, respectively. The proposed method was applied to the determination of hydrazine in water samples.